ANALISIS INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA CHANNEL YOUTUBE HANUM - Norhidayah, Siti; Ningsih, Salsabila Hady; Nurrahmi, Dwi; Adyaputri, Elvira; Jasiah, Jasiah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
In the digital age, technology-based learning media such as YouTube are a potential alternative for improving the quality and appeal of Islamic Education (PAI) learning. This study aims to analyze the innovations in PAI learning presented on Hanum's YouTube channel using Rogers' Innovation Diffusion Theory, specifically relative advantage, compatibility, complexity, trialability, and observability as the analytical framework. This study employs a qualitative method with a content analysis approach. Data were collected from educational videos on the Hanum channel that align with the PAI curriculum for junior high schools, have a minimum duration of five minutes, and include visual elements, narration, and educational presentation structure. The results indicate that the Hanum channel meets the five innovation characteristics outlined by Rogers: (1) relative advantage, through the presentation of material that is more interesting and interactive than conventional methods; (2) compatibility, with content that is relevant to the curriculum and students' psychological needs; (3) complexity, due to simple and easy-to-understand delivery; (4) trialability, as the videos can be used flexibly; and (5) observability, as seen in the effective visual structure and narrative that enhance students' understanding. Thus, the Hanum YouTube channel can be used as an innovative learning medium that supports the effectiveness and appeal of PAI learning at the junior high school level.